Potential of Borneo Acacia wood in fully biodegradable bio-composites' commercial production and application - Muhammad Khusairy, Bakri; Jayamani, E.; Sinin, Hamdan; Md. Rezaur, Rahman; Kakar, A. (Springer Link, 2019)
This review paper explores the potential of commercial production and application of Acacia wood—polylactic acid (PLA), and Acacia wood—polyhydroxyalkanoates (PHA) bio-composites. The factors affecting the mechanical and physical properties of these materials were identified and deliberated. It was found that Acacia wood has the prospective to be efficiently produced and used in Borneo. It can be used in a variety of applications, including but not limited to: fire breaker, timber resource, furniture production, soil re-conditioning, and as reinforced materials. Since, today, there is heightened awareness regarding sustainability, manufacturers are driven towards producing completely biodegradable products that are created using PLA and PHA bio-composites. This review provides an overview on the performance of the existing composites and bio-composites, and their implementation and utilization, while focusing on the Borneo region.